POLA KEMITRAAN DAN PENDAPATAN USAHATANI TOMAT BEEF DI SERENITY FARM - Nikhen Saraswati; Ktut Murniati; Adia Nugraha (Politeknik Negeri Lampung, 2021)
This study aims to analyze the partnership pattern, cost structure, farm income, and the contribution of farm income to household income tomato beef farming in Serenity Farm. This research was conducted at Serenity Farm which is located in Cibodas Village, Lembang District, West Bandung Regency. The research method used the census method. Data collected in March 2020. Partnership patterns were analyzed using descriptive analysis methods. The cost structure was analyzed by dividing each cost component by the total cost. Profit analysis based on revenue and total cost. The contribution of beef tomato farming income to household income calculated by dividing the total income of beef tomato farming by the total household income. The results showed that the partnership pattern between Serenity Farm and beef tomato farmers used the nucleus-plasma pattern, where Serenity Farm acted as the nucleus and the beef tomato farmers acted as the plasma. The cost structure of beef tomato farming in the first growing season consists of fixed costs with a percentage of 9.21% and variable costs with a percentage of 90.79%, while in planting season II fixed costs have a percentage of 8.92%, and variable costs have a percentage. 91.08%. The income of beef tomato farming in the first planting season was IDR 20,821,875 and in the second planting season was IDR 20,891,319.44. With a value of R / C> 1. The contribution of beef tomato farming income to farmer household income was 59.46% (Rp. 41,713,194.44 / year).